Betaine regulates the gut-liver axis: a therapeutic approach for chronic liver diseases - Perumal, Sathish Kumar; Arumugam, Madan Kumar; Osna, Natalia A.; Rasineni, Karuna; Kharbanda, Kusum K. (Frontiers in Nutrition, 2025)
Chronic liver disease is defined by persistent harm to the liver that might result in decreased liver function. The two prevalent chronic liver diseases are alcohol-associated liver disease (ALD) and metabolic dysfunction-associated steatotic liver disease (MASLD). There is ample evidence that the pathogenesis of these two chronic liver diseases is closely linked to gastrointestinal dysfunctions that alters the gut-liver crosstalk. These alterations are mediated through the imbalances in the gut microbiota composition/function that combined with disruption in the gut barrier integrity allows for harmful gut microbes and their toxins to enter the portal circulation and reach the liver to elicit an inflammatory response. This leads to further recruitment of systemic inflammatory cells, such as neutrophils, T-cells, and monocytes into the liver, which perpetuate additional inflammation and the development of progressive liver damage. Many therapeutic modalities, currently used to prevent, attenuate, or treat chronic liver diseases are aimed at modulating gut dysbiosis and improving intestinal barrier function. Betaine is a choline-derived metabolite and a methyl group donor with antioxidant, anti-inflammatory and osmoprotectant properties. Studies have shown that low betaine levels are associated with higher levels of organ damage. There have been several publications demonstrating the role of betaine supplementation in preventing the development of ALD and MASLD. This review explores the protective effects of betaine through its role as a methyl donor and its capacity to regulate the protective gut microbiota and maintain intestinal barrier integrity to prevent the development of these chronic liver diseases. Further studies are needed to enhance our understanding of its therapeutic potential that could pave the way for targeted interventions in the management of not only chronic liver diseases, but other inflammatory bowel diseases or systemic inflammatory conditions.